2022
DOI: 10.1002/ptr.7606
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with rosavin attenuates PM2.5‐induced lung injury in rats through antiferroptosis via PI3K/Akt/Nrf2 signaling pathway

Abstract: Inflammation and oxidative stress caused by fine particulate matter (PM2.5) increase the incidence and mortality rates of respiratory disorders. Rosavin is the main chemical component of Rhodiola plants, which exerts anti‐oxidative and antiinflammatory effects. In this research, the potential therapeutic effect of rosavin was investigated by the PM2.5‐induced lung injury rat model. Rats were instilled with PM2.5 (7.5 mg/kg) suspension intratracheally, while rosavin (50 mg/kg, 100 mg/kg) was delivered by intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Several previous studies have revealed that PM 2.5 can increase the uptake and storage of iron in cells, manifested by increased TFRC and FTH1 expression levels, ultimately accumulating iron in cells. 15,46 The same results were obtained in our study, where TFRC and FTH1 expression levels rose significantly in lung tissue after PM 2.5 exposure, and this situation was significantly alleviated after ASX intervention. SLC7A11, a cystine/glutamate xCT transport protein, is involved in forming and releasing GSH, which is crucial for the occurrence and development of ferroptosis.…”
Section: Paper Food and Functionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several previous studies have revealed that PM 2.5 can increase the uptake and storage of iron in cells, manifested by increased TFRC and FTH1 expression levels, ultimately accumulating iron in cells. 15,46 The same results were obtained in our study, where TFRC and FTH1 expression levels rose significantly in lung tissue after PM 2.5 exposure, and this situation was significantly alleviated after ASX intervention. SLC7A11, a cystine/glutamate xCT transport protein, is involved in forming and releasing GSH, which is crucial for the occurrence and development of ferroptosis.…”
Section: Paper Food and Functionsupporting
confidence: 88%
“…43,44 This indicated that there may be a link between ferroptosis and lung damage caused by PM 2.5 , which has also been confirmed in previous studies. [45][46][47] Therefore, we examined the iron accumulation level in lung tissue and the iron deathrelated protein expression to explore whether ASX can protect against PM 2.5 -induced lung injury by inhibiting ferroptosis. Our study found that the iron content significantly increased in the rat lung tissue after PM 2.5 exposure, and ASX intervention could reduce this increase.…”
Section: Paper Food and Functionmentioning
confidence: 99%
“…Pretreatment with Rosavin reduced the levels of tissue iron and MDA and increased glutathione levels in the lung tissue. Mechanistic studies showed that Rosavin upregulated the expression of Nrf2 and other ferroptosis-related proteins, whereas a specific ferroptosis agonist RSL3 was able to reverse the protective effect of Rosavin and the intracellular phosphatidylinositol kinase (PI3K) inhibitor LY294002 decreased the upregulation of Nrf2 induced by Rosavin [62]. The study suggests that Rosavin can prevent PM2.5-induced lung injury through antiferroptosis via the PI3K/Akt/Nrf2 signaling pathway.…”
Section: Respiratory Diseasesmentioning
confidence: 89%
“…In the current studies, the gavage dosage of Rosavin is approximately 50-200 mg/kg [45,62], with a maximum dosage of 360 mg/kg [38]; most intraperitoneal doses are within 10 mg/kg [56,68], with a maximum dosage of 30 mg/kg [36]. However, there are no studies to identify Rosavin's toxicity, and the systemic toxicological analysis in the liver and kidney after using Rosavin is still unclear.…”
Section: Drug Metabolism and Formulation Studies Of Rosavinmentioning
confidence: 99%
“…Tectoridin, a flavonoid from the rhizome of Belamcanda chinensis, activates the Nrf2 signaling pathway to prevent ferroptosis in lung damage [141]. Similarly, rosavin, a key glycoside from Rhodiola plants, protects against PM2.5-induced lung injury by activating the PI3K/Akt/Nrf2 pathway to inhibit ferroptosis [142]. Astragaloside IV (Ast-IV), a principal glycosidic molecule found in astragalus, effectively modulates ferroptosis and curbs iron-dependent ROS buildup in ALI triggered by PM2.5.…”
Section: Acute Lung Injurymentioning
confidence: 99%